Leading change in your school : how to conquer myths, build commitment, and get results - Reeves, Douglas B., 1953- (Alexandria, VA : ASCD, 2009)
An exploration of change initiatives in schools that provides real life examples and advice on creating conditions for change and planning, implementing, and sustaining it.
"ASCD product #109019"--T.p. verso.
Includes bibliographical references (p. 164-170) and index.
Professional
Keywords: Educational change -- United States; Educational leadership -- United States; School improvement programs -- United States; School management and organization -- United States; Educational change; Educational leadership; School improvement programs; Schools -- Administration -- United States